Determinants of the need for respite according to the characteristics of informal carers of elderly people at home: results from the 2015 French national survey - Wilfried GUETS; Lionel PERRIER (BMC, 2021)
Abstract Background The demographic and social changes associated with population aging and the increasing incidence of chronic diseases underscore the importance of the role of informal carers. The number of informal carers is increasing and negative consequences associated with providing care, such as burnout, are known. However the influence of socioeconomic and psychological factors on the need for respite have not been well characterized to date. Informal care represents an essential component of health care systems and long-term care. The purpose of this study was to shed light on how the characteristics of informal carers affect the need for respite. Methods We used data from a nationally representative survey, Capacités Aides et Resources des Seniors (CARE - ménage), collected in 2015 by the National Institute for Statistics and Economic Studies (INSEE) and the Directorate for Research, Studies, Assessment and Statistics (DREES). The determinants of the need for respite among the characteristics of informal caregivers were explored using a probit model. To handle missing data, sensitivity analyses were performed using multiple imputations. Results Our study included N = 4033 dyads of informal carers and care recipients. The mean age was 61 for carers. The majority of carers were female, married, the child of the care recipient. Almost 27% reported a need for respite. A worse health status, feeling of loneliness, having a lack of time for oneself and needing to provide more than 30 h of care per month very significantly increased the need for respite irrespective of whether or not the carer lived with the care recipient (p < 0.01). Providing care to other persons was likely to induce a greater need for respite (p < 0.01). Cohabitation of the informal carer and the care recipient was likely to increase the need for respite (p < 0.05). Conversely, however, being closely acquainted with the care recipient showed a reduced need for respite in comparison with that of carers who are married to their care recipient (p < 0.05). Conclusions These findings provide useful information for policymakers, physicians and other health professionals for reducing carers' risk of exhaustion and burnout and for referring carers to the relevant service, e.g. psychological intervention, respite care support, training support and education support.